Scabies escaping detection until dermoscopy was applied - Aimilios Lallas; Zoe Apalla; Elizabeth Lazaridou; Elena Sotiriou; Efstratios Vakirlis; Dimitrios Ioannides (Mattioli1885, 2017)
Dermoscopy is already considered a fairly established method for diagnosing scabies. This is because dermoscopy enables the visualisation both of the burrow and the mite itself, forming the so-called "jet with a contrail" structure. In the present report we present an extraordinary case of a patient with scabies lesions on the face and neck, which was misdiagnosed during sequential visits and underwent unnecessary surgical diagnostic procedures. Finally, the diagnostic problem was solved when dermoscopy was applied.